Small scaled plastics molding extrusion / Ilya Adila Ahmad Mahayuddin - Ahmad Mahayuddin, Ilya Adila (2023)
Plastic extrusion is a higher production technology that involves melting and molding a polymer material in a continuous process after adding the proper additives. Nowadays, most raw materials, such as aluminum, are relatively expensive due to the manufacturing procedures required. To save money, this Small Scaled Plastics Molding Extrusion will assist users in obtaining lower-cost raw materials to complete their projects using only crushed plastic. Extrusion of plastic profiles allows us to produce a large number of parts in a short amount of time at a low cost. Extrusion is a fast and efficient method of producing continuous shapes of varying lengths. With minimal waste, large quantities of products can be produced. Furthermore, the material used is heated and forced through a shaped cut in a metal plate during the plastic extrusion process, resulting in a continuous form that may be stretched and then cooled to set. Once cooled, these linear products can be trimmed to length to make plastic pieces. Extrusion of plastics is a high-volume manufacturing method that involves melting raw plastic and forming it into a continuous shape. Pipes, tubing, and door profiles are examples of items with a continuous profile that students can utilize to produce for their final year project for the next year. It is because of the project's low cost when they used this plastic molding. In future, students just need to find and collect used plastics and mold them so that they can use it to create something such as table, pipe, and chair for their project. Then, a small scale of extrusion molding is projected to shape at the end of the project. The size of the molding plastic extrusion product is determined by the equipment that we have set up.